TI_GERICHTE 12.2006.118 vom 13. August 2007 , Prescrizione nelle more della causa - perenzione processuale - decesso di una parte - TI Tribunale d'appello (2007)
Prescrizione nelle more della causa - perenzione processuale - decesso di una parte